Respuesta :

Answer is :Y is the easiest first using second equation . Ill show you steps below why . If you want to see the steps .



2x+4y=26


3x+y = 9


So first solve second equation


3x+y=9


Y= -3x+9


Now plug into first equation


2x+4y=26


2x+4(-3x+9)=26


2x-12x+36=26


-10x+36=26


-10x= 26-36


-10x= -10


X=1


So now solve for y in second equation



Y= -3x+9


Y= -3(1)+9


Y= -3+9


Y= 6



So if you were to be asked answer in point (1,6).

Answer: the easiest to solve for is y in the second equation.

Explanation: To solve for the y in the second equation, only one step is needed, namely subtracting 3x from both sides:

3x + y = 9

y = 9 - 3x

This is unlike the rest of the options, which require at least two operations.

ACCESS MORE